PENENTUAN POTENSI PENGEMBANGAN KAWASAN BERORIENTASI TRANSIT DI SEKITAR TITIK TRANSIT MRT JAKARTA - Irwan, Nadya Prasanti (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2023)
Abstract Jakarta as the center of government in Indonesia has the characteristics of diversity of land use and high population density, supported by lot of investments in the development of mass public transportation, which makes Jakarta one of the compact cities in Indonesia. Integration between modes of transportation and the surrounding environment is necessary for Jakarta’s urban planning. Transit-oriented development is part of the compact city planning concept that can be applied to development in Jakarta. This study aims to determine the potential for the development of transit-oriented areas around the Jakarta Mass Rapid Transit Station within a radius of 800 m from the center of the transit node at each station. Potential locations are determined using the Analytical Hierarchy Process method on several variables forming the criteria for the development of an ideal transit-oriented area. This study shows that the areas with the most potential to be developed with the concept of transit-oriented development are Bundaran HI Station, Dukuh Atas Station, and Asean Station. Keywords: transit-oriented area development; mass rapid transit; compact city; public transit Abstrak Jakarta sebagai pusat pemerintahan di Indonesia memiliki karakteristik keberagaman penggunaan lahan dan kepadatan penduduk yang tinggi dan didukung dengan banyaknya investasi pembangunan transportasi umum massal, yang menjadikan Jakarta sebagai salah satu kota kompak di Indonesia. Integrasi antara moda transportasi dan lingkungan sekitar diperlukan untuk perencanaan Kota Jakarta.pengembagan kawasan berorientasi transit merupakan bagian konsep tata kota kompak yang dapat diterapkan pada pembangunan di Jakarta. Penelitian ini bertujuan untuk mengetahui potensi pengembagan kawasan berorientasi transit di sekitar Stasiun Mass Rapid Transit Jakarta dalam radius 800 m dari pusat simpul transit di setiap stasiun. Lokasi potensial ditentukan dengan menggunakan metode Analytical Hierarchy Process pada beberapa variabel pembentuk kriteria pengembagan kawasan berorientasi transit yang ideal. Studi ini menunjukkan bahwa kawasan yang paling potensial untuk dikembangkan dengan konsep pengembagan kawasan berorientasi transit adalah Stasiun Bundaran HI, Stasiun Dukuh Atas, dan Stasiun Asean. Kata-kata kunci: pengembangan kawasan berorientasi transit; mass rapid transit; kota kompak; transportasi umum